EFFECT OF HEAT TREATMENT ON THE CORROSION RATE OF S45C STEEL - Anisa D. I; Prayitno, Dody; Riyono , Joko; Aji, Daisman P. B. (Konsorsium Cendekiawan Indonesia, 2020)
Parts of North Jakarta are at risk of tidal floods as heavy rainfall hits Jakarta. The Jakarta Regional Disaster Mitigation Agency (BPBD) recorded an increase in water level at the Pasar Ikan floodgate in North Jakarta to 210 centimeters. The floods inundated homes and vehicles such as cars. The parts of car such as S45C steel shaft will corrode when it is in seawater. For a good performance in application a S45C steel should be heat treated (hardening and/or annealing). The aim of this research is to investigate the effect of heat treatment on the corrosion rate of S45C steel in the sea water. A S45C steel plate was cut and machined into some smaller pieces of plates for the experimental samples. The samples were hardened and annealed. Then the samples were immersed in solution of NaCl (5%) and the corrosion rate was obtained by using the weight loss method. Next the corrosion rate data were analysed by MATLAB software. The results show that in hardening process. increasing temperature of heating from 800 oC to 900 oC does not affect the corrosion rate. The annealing effect is reducing corrosion rate yet increasing time of exposure does not affect the corrosion rate.